Simplified Inhouse Nanoweb Membrane Enrichment Coupled Viral Whole Genome Shotgun Metagenomics Approach for Waste Water Surveillance - Shashi Sharma; Pushpendra Kumar Sharma; Ekta Gupta; Paban Kumar Dash; Ambuj Srivastava (Food and Environmental Virology, 2026)

Molecular basis of fertility restoration: roles of Rf, RFL, PPR, and mTERF genes in wheat and other cereal crops - Pushpendra K. Gupta; Harindra S. Balyan; Sourabh Kumar (Euphytica, 2026)

Twenty years of wheat genomics (2005–2025) - Pushpendra Kumar Gupta (Trends in Plant Science, 2026)

Dynamic performance evaluation of evolutionary multi-objective optimization algorithms for gait cycle optimization of a 25-DOFs NAO humanoid robot - Pushpendra Gupta; Dilip Kumar Pratihar; Kalyanmoy Deb (Swarm and Evolutionary Computation, 2025)

Conditional QTL analysis of grain yield and eight yield-contributing traits under drought stress in wheat (Triticum aestivum L.) - Vijay Gahlaut; Vandana Jaiswal; Harindra Singh Balyan; Pushpendra Kumar Gupta (Plant Physiology Reports, 2025)

MicroRNAs associated with spot blotch in bread wheat (Triticum aestivum) - Neeraj Kumar Vasistha; Sandeep Sharma; Vinod Kumar Mishra; Tinku Gautam; Gautam Saripalli; Sunita Pal; Pushpendra Kumar Gupta (Physiological and Molecular Plant Pathology, 2025)

Transcriptome analysis for the identification of spot blotch responsive genes and miRNAs in wheat - Neeraj Kumar Vasistha; Archita Tandon; Sunita Pal; Sandeep Sharma; Vinod Kumar Mishra; Pushpendra Kumar Gupta (Physiological and Molecular Plant Pathology, 2025)

Identification and characterization of sulphotransferase (SOT) genes for tolerance against drought and heat in wheat and six related species - Jyoti Chaudhary; Himanshi Gangwar; Vandana Jaiswal; Pushpendra Kumar Gupta (Molecular Biology Reports, 2024)

Experimental analysis of thermal energy efficient clay brick incorporated with phase change material and insulation - Pushpendra Kumar Singh Rathore; Bhaskar Patel; Manglesh Kumar Gupta; Basant Singh Sikarwar; R.K. Sharma (Process Safety and Environmental Protection, 2024)

Comparative analysis of VMT genes/proteins in selected plant species with emphasis on bread wheat (Triticum aestivum L.) - Hemant Sharma; Shayaba; Rahul Kumar; Jitendra Kumar; Deepa Bhadana; Ritu Batra; Rakhi Singh; Sachin Kumar; Joy K Roy; Harindra S. Balyan; Pushpendra K. Gupta (Genes & Genomics, 2023)

Identification and characterization of RuvBL DNA helicase genes for tolerance against abiotic stresses in bread wheat (Triticum aestivum L.) and related species - Jyoti Chaudhary; Tinku Gautam; Vijay Gahlaut; Kalpana Singh; Sourabh Kumar; Ritu Batra; Pushpendra Kumar Gupta (Functional & Integrative Genomics, 2023)

Further studies on nicotianamine aminotransferase (NAAT) genes involved in biofortification in bread wheat (Triticum aestivum L.) - Tinku Gautam; Irfat Jan; Ritu Batra; Kalpana Singh; Renu Pandey; Pradeep Kumar Sharma; Harindra Singh Balyan; Pushpendra Kumar Gupta (Plant Gene, 2023)

QTL analysis for nitrogen use efficiency in wheat (Triticum aestivum L.) - Rakhi Singh; Gautam Saripalli; Anuj Kumar; Tinku Gautam; Susheel Kumar Singh; Vijay Gahlaut; Sachin Kumar; Prabina Kumar Meher; Rajendra Prasad Mishra; Vinod Kumar Singh; Pradeep Kumar Sharma; Harindra Singh Balyan; et al. (Euphytica, 2023)

BS-Seq reveals major role of differential CHH methylation during leaf rust resistance in wheat (Triticum aestivum L.) - Kalpana Singh; Gautam Saripalli; Tinku Gautam; Pramod Prasad; Neelu Jain; Harindra Singh Balyan; Pushpendra Kumar Gupta (Molecular Genetics and Genomics, 2022)

GWAS for main effects and epistatic interactions for grain morphology traits in wheat - Parveen Malik; Jitendra Kumar; Shiveta Sharma; Prabina Kumar Meher; Harindra Singh Balyan; Pushpendra Kumar Gupta; Shailendra Sharma (Physiology and Molecular Biology of Plants, 2022)

Meta-QTLs, ortho-MetaQTLs and candidate genes for grain Fe and Zn contents in wheat (Triticum aestivum L.) - Rakhi Singh; Gautam Saripalli; Tinku Gautam; Anuj Kumar; Irfat Jan; Ritu Batra; Jitendra Kumar; Rahul Kumar; Harindra Singh Balyan; Shailendra Sharma; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2022)

Correction to: WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Meta-QTLs, ortho-MQTLs and candidate genes for nitrogen use efficiency and root system architecture in bread wheat (Triticum aestivum L.) - Dinesh Kumar Saini; Yuvraj Chopra; Neeraj Pal; Amneek Chahal; Puja Srivastava; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2021)

WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Correction to: QTL analysis and fine mapping of a QTL for yield‑related traits in wheat grown in dry and hot environments - Habtamu Tura; James Edwards; Vijay Gahlaut; Melissa Garcia; Beata Sznajder; Ute Baumann; Fahimeh Shahinnia; Matthew Reynolds; Peter Langridge; Harindra Singh Balyan; Pushpendra K. Gupta; Thorsten Schnurbusch; et al. (Theoretical and Applied Genetics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00122-021-03792-4

An assessment of global satellite‐based precipitation datasets in capturing precipitation extremes: A comparison with observed precipitation dataset in India - Vivek Gupta; Manoj K. Jain; Pushpendra K. Singh; Vishal Singh (International Journal of Climatology, 2020)
The availability of global satellite‐based precipitation datasets provides an asset to accomplish precipitation dependent analysis where gauge based precipitation datasets are not available or limited. In this study, we have taken three most popular and globally accepted satellite‐based daily gridded (0.25° × 0.25°) precipitation datasets such as Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), Satellite Soil Moisture to Rain (SM2RAIN‐ASCAT) and Tropical Rainfall Measuring Mission (TRMM now available as Global Precipitation Measurement [GPM]) for 10 years (2007–2016) time‐series durations to test their reliability across India. The India Meteorological Department (IMD) observed daily gridded (0.25° × 0.25°) precipitation data have been taken as reference data to compare the other three satellite‐based gridded precipitation datasets by developing standard extreme precipitation indices (SEPIs). The precipitation extremity has been tested in the wet season (June–July–August–September) and throughout the year. We have also analysed the extreme behaviour of precipitation (in both upper and lower tails) using quantile‐quantile (Q–Q) regression analysis after selecting 33 random precipitation grids across India. The overall analysis results showed that all satellite‐based datasets have significant spatial heterogeneity in estimating precipitation extremes accurately which varies across India. Among all satellite‐precipitation datasets, TRMM found closer to IMD than SM2RAIN‐ASCAT and CHIRPS. The frequency based SEPIs showed that CHIRPS, TRMM and SM2RAIN‐ASCAT have similarities to IMD precipitations. The intensity‐based SEPIs show that TRMM and CHIRPS have significant similarities with IMD precipitations. The wet season‐based analysis results showed that TRMM and CHIRPS are closer to IMD precipitations than SM2RAIN‐ASCAT satellite‐precipitations. Overall TRMM and CHIRPS datasets performed well across most regions in India, while SM2RAIN‐ASCAT dataset has performed poorly in India, especially for extreme precipitation cases. Q–Q plots show that each satellite‐based precipitation dataset captured most of extreme cases in different quantile intervals with respect to IMD precipitation; however, SM2RAIN‐ASCAT has slightly under‐performed at many regions in India.

In vitro evaluation to intensify the differential morphogenetic response through plant growth regulators and antibiotic supplementation in sugarcane - Devendra Kumar; Rakesh Singh Sengar; Nisha Malik; Manoj Kumar Yadav; Shalani Gupta; Pooran Chand; Gopal Singh; Pushpendra Kumar (Plant Physiology Reports, 2020)

Genetics of yield, abiotic stress tolerance and biofortification in wheat (Triticum aestivum L.) - Pushpendra Kumar Gupta; Harindra Singh Balyan; Shailendra Sharma; Rahul Kumar (Theoretical and Applied Genetics, 2020)

QTL analysis and fine mapping of a QTL for yield-related traits in wheat grown in dry and hot environments - Habtamu Tura; James Edwards; Vijay Gahlaut; Melissa Garcia; Beata Sznajder; Ute Baumann; Fahimeh Shahinnia; Matthew Reynolds; Peter Langridge; Harindra Singh Balyan; Pushpendra K. Gupta; Thorsten Schnurbusch; et al. (Theoretical and Applied Genetics, 2020)
Genetic control of grain yield and phenology was examined in the Excalibur/Kukri doubled haploid mapping population grown in 32 field experiments across the climatic zones of southern Australia, India and north-western Mexico where the wheat crop experiences drought and heat stress. A total of 128 QTL were identified for four traits: grain yield, thousand grain weight (TGW), days to heading and grain filling duration. These QTL included 24 QTL for yield and 27 for TGW, showing significant interactions with the environment ( Q * E ). We also identified 14 QTL with a significant, small main effects on yield across environments. The study focussed on a region of chromosome 1B where two main effect QTL were found for yield and TGW without the confounding effect of phenology. Excalibur was the source of favourable alleles: QYld.aww - 1B.2 with a peak at 149.5–150.1 cM and QTgw.aww - 1B at 168.5–171.4 cM. We developed near isogenic lines (NIL) for the interval including QYld.aww - 1B.2 and QTgw.aww - 1B and evaluated them under semi-controlled conditions. Significant differences in four pairs of NIL were observed for grain yield but not for TGW, confirming a positive effect of the Excalibur allele for QYld.aww - 1B.2 . The interval containing QYld.aww - 1B.2 was narrowed down to 2.9 cM which corresponded to a 2.2 Mbp genomic region on the chromosome 1B genomic reference sequence of cv. Chinese Spring and contained 39 predicted genes.

Hybrid wheat: past, present and future - Pushpendra Kumar Gupta; Harindra Singh Balyan; Vijay Gahlaut; Gautam Saripalli; Bijendra Pal; Bhoja Raj Basnet; Arun Kumar Joshi (Theoretical and Applied Genetics, 2019)

Validation of QTL for grain weight using MAS-derived pairs of NILs in bread wheat (Triticum aestivum L.) - Supriya Kumari; Reyazul Rouf Mir; Sandhya Tyagi; Harindra Singh Balyan; Pushpendra Kumar Gupta (Journal of Plant Biochemistry and Biotechnology, 2019)

Wheat cytogenetics and cytogenomics: the present status - Pushpendra K. Gupta; Neeraj K. Vasistha (The Nucleus, 2018)

Genetics of Fe, Zn, β-carotene, GPC and yield traits in bread wheat (Triticum aestivum L.) using multi-locus and multi-traits GWAS - Jitendra Kumar; Gautam Saripalli; Vijay Gahlaut; Neha Goel; Prabina Kumar Meher; Kaushlesh Kumar Mishra; Prafulla Chandra Mishra; Deepmala Sehgal; Prashant Vikram; Carolina Sansaloni; Sukhwinder Singh; Pradeep Kumar Sharma; et al. (Euphytica, 2018)

QTL mapping for some grain traits in bread wheat (Triticum aestivum L.) - Supriya Kumari; Vandana Jaiswal; Vinod Kumar Mishra; Rajneesh Paliwal; Harindra Singh Balyan; Pushpendra Kumar Gupta (Physiology and Molecular Biology of Plants, 2018)

Biology of B. sorokiniana (syn. Cochliobolus sativus) in genomics era - Pushpendra K. Gupta; Neeraj K. Vasistha; Rashmi Aggarwal; Arun K. Joshi (Journal of Plant Biochemistry and Biotechnology, 2017)

Stable carbon and oxygen isotope study on benthic foraminifera: Implication for microhabitat preferences and interspecies correlation - Ajoy K Bhaumik; Shiv Kumar; Shilpi Ray; G K Vishwakarma; Anil K Gupta; Pushpendra Kumar; Kalachand Sain (Journal of Earth System Science, 2017)

Transcription factors involved in drought tolerance and their possible role in developing drought tolerant cultivars with emphasis on wheat (Triticum aestivum L.) - Vijay Gahlaut; Vandana Jaiswal; Anuj Kumar; Pushpendra Kumar Gupta (Theoretical and Applied Genetics, 2016)

AGPase: its role in crop productivity with emphasis on heat tolerance in cereals - Gautam Saripalli; Pushpendra Kumar Gupta (Theoretical and Applied Genetics, 2015)

Stage-specific reprogramming of gene expression characterizes Lr48-mediated adult plant leaf rust resistance in wheat - Raman Dhariwal; Vijay Gahlaut; Bhaganagare R. Govindraj; Dharmendra Singh; Saloni Mathur; Shailendra Vyas; Rajib Bandopadhyay; Jitendra Paul Khurana; Akhilesh Kumar Tyagi; Kumble Vinod Prabhu; Kunal Mukhopadhyay; Harindra Singh Balyan; et al. (Functional & Integrative Genomics, 2015)

Chromosome mapping of four novel mutants in bread wheat (Triticum aestivum L.) - Priyanka Agarwal; Vandana Jaiswal; Sachin Kumar; Harindra Singh Balyan; Pushpendra Kumar Gupta (Acta Physiologiae Plantarum, 2015)

A multi-step phosphorelay two-component system impacts on tolerance against dehydration stress in common wheat - Vijay Gahlaut; Saloni Mathur; Raman Dhariwal; Jitendra P. Khurana; Akhilesh K. Tyagi; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2014)

New molecular scaffolds for the design of Alzheimer’s acetylcholinesterase inhibitors identified using ligand- and receptor-based virtual screening - Nitin Chitranshi; Shipra Gupta; Pushpendra Kumar Tripathi; Prahlad Kishore Seth (Medicinal Chemistry Research, 2013)

Targeted spatio-temporal expression based characterization of state of infection and time-point of maximum defense in wheat NILs during leaf rust infection - Dharmendra Singh; Govindraj Bhaganagare; Rajib Bandopadhyay; Kumble Vinod Prabhu; Pushpendra Kumar Gupta; Kunal Mukhopadhyay (Molecular Biology Reports, 2012)

QTL identification for molecular breeding of fibre yield and fibre quality traits in jute - Moumita Das; Sumana Banerjee; Niladri Topdar; Avijit Kundu; Reyazul Rouf Mir; Debabrata Sarkar; Mohit K. Sinha; Harindra S. Balyan; Pushpendra K. Gupta (Euphytica, 2012)

Development of SSR markers and construction of a linkage map in jute - MOUMITA DAS; SUMANA BANERJEE; RAMAN DHARIWAL; SHAILENDRA VYAS; REYAZUL R. MIR; NILADRI TOPDAR; AVIJIT KUNDU; JITENDRA P. KHURANA; AKHILESH K. TYAGI; DEBABRATA SARKAR; MOHIT K. SINHA; HARINDRA S. BALYAN; et al. (Journal of Genetics, 2012)

Development of large-scale AFLP markers in jute - Moumita Das; Sumana Banerjee; Niladri Topdar; Avijit Kundu; Debabrata Sarkar; Mohit K. Sinha; Harindra S. Balyan; Pushpendra K. Gupta (Journal of Plant Biochemistry and Biotechnology, 2011)

A preliminary genetic analysis of fibre traits and the use of new genomic SSRs for genetic diversity in jute - Reyazul R. Mir; Sachin Rustgi; Shailendra Sharma; Ravinder Singh; Aakash Goyal; Jitendra Kumar; Anupama Gaur; Akhilesh K. Tyagi; Haseena Khan; Mohit K. Sinha; Harindra S. Balyan; Pushpendra Kumar Gupta (Euphytica, 2008)

Molecular approaches for improvement of medicinal and aromatic plants - Jitendra Kumar; Pushpendra Kumar Gupta (Plant Biotechnology Reports, 2008)

QTL analysis for some quantitative traits in bread wheat - Kumar Gupta Pushpendra; Singh Balyan Harindra; Laxminarayan Kulwal Pawan; Kumar Neeraj; Kumar Ajay; Rouf Mir Reyazul; Mohan Amita; Kumar Jitendra (Journal of Zhejiang University-SCIENCE B, 2007)

QTL analysis for grain weight in common wheat - Neeraj Kumar; Pawan L. Kulwal; Anupama Gaur; Akhilesh K. Tyagi; Jitendra P. Khurana; Paramjit Khurana; Harindra S. Balyan; Pushpendra K. Gupta (Euphytica, 2006)

Physical molecular maps of wheat chromosomes - Aakash Goyal; Rajib Bandopadhyay; Pierre Sourdille; Takashi R. Endo; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2005)

Gene networks in hexaploid wheat: interacting quantitative trait loci for grain protein content - Pawan Kulwal; Neeraj Kumar; Ajay Kumar; Raj Kumar Gupta; Harindra Singh Balyan; Pushpendra Kumar Gupta (Functional & Integrative Genomics, 2005)

Linkage disequilibrium and association studies in higher plants: Present status and future prospects - Pushpendra K. Gupta; Sachin Rustgi; Pawan L. Kulwal (Plant Molecular Biology, 2005)

Characterization of microsatellites and development of chromosome specific STMS markers in bread wheat - Rajeev K. Varshney; Alok Kumar; Harindra S. Balyan; Joy K. Roy; Manoj Prasad; Pushpendra K. Gupta (Plant Molecular Biology Reporter, 2000)